A Comparative Study On Parent And Resistant MCF-7 Cells On Migration Characteristics With Regards To Bioactive Glass Treatment - Jallow, Haruna S (2019)
Introduction: Breast cancer is one of the leading causes of mortality worldwide, particularly among women. It accounts for one third of mortality and is the second most common cancer in the world. The 45S5 bioactive glass (BG) is predominantly used in the orthopaedic and dentistry field for bone and tissue regeneration. Recently, it is being tested as a mode of drug delivery particularly in cancer therapy. Objective: To perform a comparative study on parent and resistant breast cancer cell lines (MCF-7) migration with 4555 bioactive glass. Methods: BG was synthesised using sol-gel method. Wound healing assay was done to determine closure of wound area at different time-points. Each cell line was grown in 24-well plates and treated with different concentration of BG and standard chemotherapy drug vinblastine. Wound area was analysed using Image J and repeated measures ANOVA used to analyse the obtained data. Results and Discussion: Findings suggest 2 mg/ml BG promoted migration and migration of parent and resistant MCF- 7 breast cancer cells. While at higher concentration with 4 mg/ml BG, 8 mg/ml BG and vinblastine caused inhibition of parent and resistant MCF-7. There was no significant difference of closure area between the controls and 2 mg/ml BG treated cells. Significant difference was detected between the controls of parent and resistant MCF-7 cells with 4 mg/ml BG, 8 mg/ml BG and vinblastine treated breast cancer cells. Furthermore, there was no significant difference between ≥ 4 mg/ml BG treated cells and vinblastine. Conclusion: Bioactive glass of ≥ 4 mg/ml can be useful as a prospective inhibitory agent in breast cancers or can be doped as an adjuvant to standard chemotherapy.